COMPARATIVE ANALYSIS OF THREE-DIMENSIONAL NANOSTRUCTURE OF POROUS BIOCOMPATIBLE SCAFFOLDS MADE OF RECOMBINANT SPIDROIN AND SILK FIBROIN FOR REGENERATIVE MEDICINE - O. I. Agapova; A. E. Efimov; M. M. Moisenovich; V. G. Bogush; I. I. Agapov (Вестник трансплантологии и искусственных органов)
Aim. To perform a comparison of three-dimensional nanostructure of porous biocompatible scaffolds made of fibroin Bombix mori and recombinant spidroin rS1/9. Materials and methods. Three-dimensional porous scaffolds were produced by salt leaching technique. The comparison of biological characteristics of the scaffolds shows that adhesion and proliferation of mouse fibroblasts in vitro on these two types of scaffolds do not differ significantly. Comparative experiments in vivo show that regeneration of bone tissue of rats is faster with implantation of recombinant spidroin scaffolds. Three-dimensional nanostructure of scaffolds and interconnectivity of nanopores were studied with scanning probe nanotomography (SPNT) to explain higher regenerative activity of spidroin-based scaffolds. Results. Significant differences were detected in the integral density and volume of pores: the integral density of nanopores detected on 2D AFM images is 46 μm–2    and calculated volume porosity is 24% in rS1/9-based scaffolds; in fibroin-based three-dimensional structures density of nanopores and calculated volume porosity were 2.4 μm–2  and 0.5%, respectively. Three-dimensional reconstruction system of nanopores and clusters of interconnected nanopores in rS1/9-based scaffolds showed that volume fraction of pores interconnected in percolation clusters is 35.3% of the total pore volume or 8.4% of the total scaffold volume. Conclusion. Scanning probe nanotomography method allows obtaining unique information about topology of micro – and nanopore systems of artificial biostructures. High regenerative activity of rS1/9-based scaffolds can be explained by higher nanoporosity of the scaffolds.